Information Theoretic Methods for Future Communication Systems - Günlü, Onur; Schaefer, Rafael F.; Boche, Holger; Poor, H. Vincent (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint focuses on information and coding theoretic metrics, analyses, and methods applied to future communication and computation systems. Analyses of learning algorithms and information security problems are studied in detail. The main themes addressed are multiple access channels, interference channels, and delay-Doppler domain analysis, as well as secure and private compression, matrix multiplication, and transmission methods.